ARE ANTIBIOTICS OF ANY USE IN THE MANAGEMENT OF GRANULOMA ANNULARE IN CHILDREN? - Chia, Germaine; Ahmed, Leila; Oligbu, Peter; Odeigah, Louis; Oligbu, Godwin (African Journal of Infectious Diseases (AJID), 2019)
Background: Granuloma annulare (GA) is a benign inflammatory dermatosis of unknown cause, of which generalised granuloma annulare (GGA) is a subtype that tends to be resistant to treatment. Various antibiotics have been used to treat GGA, the most recent being combination therapy with rifampicin, ofloxacin and minocycline (ROM). This study aims to explore the efficacy of antibiotics in treating GGA, and whether antibiotics may be useful in children with GGA. Materials and Methods: A systematic review of literature published from 1947 to 2017 was undertaken in order to evaluate the use of antibiotics in treating GGA. Data on characteristics of children with GGA were extracted. Eligible studies were then qualitatively analysed. Results: Seven hundred and ninety (790) potential studies were identified, of which 16 were eligible for inclusion in the final analysis. Of these 16 studies, majority were case studies (n=9, 56.3%), with 2 case series (12.5%), 2 retrospective studies (12.5%) and 3 open-label prospective studies (18.8%). Main antibiotic treatments reported were either monthly combination therapy of rifampicin, ofloxacin and minocycline (ROM), or monotherapy with dapsone or doxycycline. Out of a total of 158 patients with GA, 72 patients (45.6%) were treated with antibiotics. Of the 72, 48.6% (n=35) of these patients had GGA while 4 were children; two with GA (2 with GGA), all of whom were treated with dapsone. Conclusion: There is paucity of evidence to support the use of antibiotics in the treatment of GGA in children. Although ROM has shown promising results in adults, more studies are needed to validate these findings in children.